PERAN GURU SEBAGAI PEMBIMBING DALAM PENANAMAN KARAKTER TANGGUNG JAWAB DAN KEPEDULIAN MELALUI PEMBELAJARAN TEMATIK BERMUATAN PPKN SISWA KELAS VA SD NEGERI 68 KOTA BENGKULU - Tri Dianti; Puspa Djuwita (JURIDIKDAS, 2023)
This study aims to describe the teacher's role as a mentor in instilling the character of responsibility and caring through thematic learning with PPKN content in class VA students at SD Negeri 68 Bengkulu City. This study uses a qualitative type. The subjects of this study were students, VA class teachers and school principals. The research instrument uses observation guidelines, interviews and documentation. Data collection techniques using observation, interviews and documentation. The data obtained were analyzed through data collection, data reduction, data presentation, conclusion/verification. The results of this study are: a) The role of the teacher as a guide in planning learning objectives is carried out by the teacher in accordance with the analysis of the curriculum, KI and KD which have been analyzed to guide Grade VA students in instilling a character of responsibility. and care. The teacher has also made a lesson plan, in carrying out teacher learning guided by the lesson plan that was made and the teacher mastered the material during the teaching and learning process. b) the role of the teacher as a guide in interpreting learning in inculcating the character of responsibility and caring, namely what the teacher does in learning through the habituation method, by instilling good behavior habits, doing assignments on time, class pickets according to the schedule, doing assignments individually, doing work group together and dispose of trash in its place. c) in the evaluation of learning to inculcate the character of responsibility and care, the teacher evaluates attitudes every day during learning or after learning.